Comparative toxicity of cypermethrin and a commercial formulation on Rhinella arenarum larval development (Anura: Bufonidae) - Svartz, Gabriela Veronica (2013)
In this study we reported the effects of cypermethrin (CY), a growing use insecticide, comparing the toxicity of the active ingredient (AI) and a commercial formulation (CF) on a non-target organism, Rhinella arenarum. The results showed a highly significant increase (p<0.05) in the toxicity of both substances over time, obtaining a 96 h LC-50 of 28.07 mg CY/L and 11.20 mg CY/L, and a 336 h LC-50 of 0.0048 mg CY/L and 0.00065 mg CY/L, for AI and CF respectively. Furthermore, the toxicity of CF was greater than AI at all exposure periods, reaching up to 7 times. The main sublethal effects were associated with alterations in behaviour as hyperkinesia and spasmodic contractions up to total absence of movements. Considering these results and the obtained by means of the risk assessment conducted, we can conclude that this pesticide represents a potential direct risk considering lethality, or indirect by means of its sublethal effects for the survival of this amphibian in agroecosystems.